2011
DOI: 10.1016/j.neuron.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The Pore of the Voltage-Gated Proton Channel

Abstract: SUMMARY In classical tetrameric voltage-gated ion channels four voltage-sensing domains (VSDs), one from each subunit, control one ion permeation pathway formed by four pore domains. The Hv proton channel has a different architecture, containing a VSD, but lacking a pore domain. Since its location is not known, we searched for the Hv permeation pathway. We find that mutation of the S4 segment’s third arginine R211 (R3) compromises proton selectivity, enabling conduction of a metal cation and even of the large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 36 publications
6
93
0
Order By: Relevance
“…We found that salt-bridge networks and electrostatic potential maps are the signatures of activation states and that the activated channel is compatible with proton conduction. These results are in general agreement with experimental mutagenesis (35,58) and zinc accessibility (34) studies.…”
Section: S1supporting
confidence: 91%
“…We found that salt-bridge networks and electrostatic potential maps are the signatures of activation states and that the activated channel is compatible with proton conduction. These results are in general agreement with experimental mutagenesis (35,58) and zinc accessibility (34) studies.…”
Section: S1supporting
confidence: 91%
“…The precise nature and location of the proton conduction pathway in Hv1 channels is still under debate. It was suggested in recent studies that this pathway is constructed by two water vestibules at the intra-and extracellular portion of the channel connected by a narrow bottleneck where the proton selectivity occurs (10,12,13). Musset et al showed that the negatively charged residue Asp160 in S1 (Asp112 in hHv1) acts as a proton-selectivity filter (12).…”
Section: Discussionmentioning
confidence: 99%
“…Musset et al showed that the negatively charged residue Asp160 in S1 (Asp112 in hHv1) acts as a proton-selectivity filter (12). Berger and Isacoff suggested that the bottleneck is composed of the interaction of a negatively charged residue in the S1 (D112 in hHv1 and Asp160 in Ci-Hv1) and the third arginine in the S4 (Arg211 in hHv1 and Arg261 in Ci-Hv1) (13 In the open state, water wires can form, but they are fairly rare and short lived. Instead, we propose that proton permeation occurs by a mixed mechanism, where both protonatable residues and water molecules form the permeation pathway in open Hv1 channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations